Microenvironment Dependent Photobiomodulation on Function-Specific Signal Transduction Pathways. (9th March 2014) - Liu, Timon Cheng-Yi; Wu, De-Feng; Zhu, Ling; Peng, P.; Liu, Long; Yang, Xiang-Bo
Abstract : Cellular photobiomodulation on a cellular function has been shown to be homeostatic. Its function-specific pathway mechanism would be further discussed in this paper. The signal transduction pathways maintaining a normal function in its function-specific homeostasis (FSH), resisting the activation of many other irrelative signal transduction pathways, are so sparse that it can be supposed that there may be normal function-specific signal transduction pathways (NSPs). A low level laser irradiation or monochromatic light may promote the activation of partially activated NSP and/or its redundant NSP so that it may induce the second-order phase transition of a function from its dysfunctional one far from its FSH to its normal one in a function-specific microenvironment and may also induce the first-order functional phase transition of the normal function from low level to high level.